Indonesia's Implementation of the Paris Agreement: A Global Governance Perspective Through the Directorate General of Climate Change Control (2020-2024) - Raihan Nur Rafi; Praja Firdaus Nuryananda (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
The purpose of this qualitative study is to identify how the implementation of the Paris Agreement has been carried out by Indonesia in the period 2020-2024 through the Directorate General of Climate Change Control under the Ministry of Environment and Forestry as Indonesia's national focal point for the UNFCCC seen through the perspective of the concept of global governance. The concept has components in the form of structural involvement from the national and subnational scope and deliberation which will produce two other components in the form of substantive and behavioral results from multistakeholder. Indonesia, in the context of implementing the Paris Agreement, needs to carry out the components contained in the concept of global governance to become a good governance. Until 2024, stakeholders in the implementation of the Paris Agreement from the national, subnational, to the community have shown behavioral changes as a result of the substantive results that have been issued by state actors involved in deliberation. At the local level, there are Masyarakat Peduli Api groups that are tasked with the prevention and management of forest and land fires. In addition, there is ProKlim which has a village-level scope managed by the Regional Government to increase community participation with the aim of reducing greenhouse gas emissions in the region. The research method used is descriptive qualitative with document study as a data collection technique.